Diagnostic accuracy of linked colour imaging versus white light imaging for early gastric cancers: a prospective, multicentre, randomized controlled trial study. (31st December 2022) - Min, Min; Sun, Xiaotian; Bai, Jianying; Zhang, Qinsheng; Yang, Xiaocui; Guo, Qiang; Wang, Rong; Wang, Bangmao; Lv, Zhiwu; Pan, Jie; Jiang, Chunmeng; Hu, Duanmin; et al.
Abstract: Background: Linked colour imaging (LCI) is a novel new image-enhanced endoscopy (IEE) technology that produces bright and vivid images. The aim of this study was to assess the ability of LCI to improve the diagnostic accuracy of early gastric cancer (EGC) relative to white light imaging (WLI). Materials and methods: We performed this study on patients undergoing screening endoscopy from 12 medical institutions in China. Patients were randomly assigned to receive WLI followed by LCI or LCI followed by WLI. The primary outcome was to compared the diagnostic accuracy between LCI and WLI for EGC/high-grade intraepithelial neoplasms. Secondary outcomes included the numbers of suspicious lesions, neoplastic lesions and examination time by using LCI detected versus using WLI. Results: A total of 1924 patients were randomly selected, and 1828 were included in the analysis. The diagnostic accuracy for EGC, which was 78.8% by using LCI and 68.4% by using WLI ( p  < .0001). More suspicious lesions were detected by LCI than by WLI ( n  = 1235 vs. 1036, p  = .031), especially among differentiated EGC ( p  = .013). LCI greatly shortened the examination time compared with WLI ( p  = .019). Conclusions: LCI has better accuracy and shorter examination time in diagnosing EGC than WLI (Clinical trial registration: NCT03092414). Key messages: Compared with white light imaging (WLI), the diagnostic accuracy, sensitivity and specificity increased by using LCI. More lesions were detected by LCI alone than by WLI alone, especially among differentiated EGC. LCI may be used as a screening tool for routine clinical observation.